Optimizing Islamic Religious Education Learning to Strengthen Religious Moderation and the Pancasila Student Profile: A Qualitative Case Study in Indonesian Elementary Schools - Siti Kusnul Khotimah; Basnang Said (Journal of General Education and Humanities, 2026)
This study explores how the optimization of Islamic Religious Education (PAI) learning strengthens religious moderation and the Pancasila Student Profile in elementary schools. Employing a qualitative descriptive case study design, the research was conducted at SDN Ciranjang 1 and SDN Nangala 1 in Cianjur Regency, Indonesia. Data were collected through in-depth interviews, classroom observations, and document analysis, and analyzed using an interactive model involving data reduction, data display, and conclusion drawing. The findings reveal that the successful internalization of moderation and civic values is strongly influenced by school management and leadership practices rather than curriculum content alone. Strategic planning, collaborative organization, experiential learning activities, and continuous evaluation enabled values such as tolerance, cooperation, and social responsibility to be embedded into daily classroom practices and school culture. Despite challenges related to time constraints, teacher readiness, and character assessment, adaptive leadership and collective participation helped sustain program implementation. The study concludes that religious moderation and character education are most effective when managed as systematic and school-wide processes. This research contributes to educational management literature by positioning PAI learning as a strategic platform for integrating religious and civic character formation in elementary education.